Women’s Control Over Economic Resources Effect to Family Welfare - Setyari, Ni Putu Wiwin; Widanta, A.A Bagus Putu; Purbadharmaja, Ida Bagus Putu (Universitas Negeri Semarang, 2018)
Within the framework of neo-classical analysis, each individual is assumed homogeneous. However, homogeneity assumption becomes incompatible when discussing human behavior. Latest literatures conclude that men and women allocated resources under their control in different ways systematically. This study was intended to see whether there is an increase in the household’s welfare if the head of household is a women and granted credit access to financial institutions. Women’s access to all financial services, is essential to allow them to benefit fully from economic opportunities. The data used came from the Indonesian Family Life Survey (IFLS) for two last waves (IFLS 2007 and 2014). Analyses were performed using fixed effect model to overcome the unobserved heterogeneity, especially in terms of the individual character. The results indicated that the credit received by the female head of households can significantly increase household income. These results support the policy of increasing women empowerment in order to improve family welfare.